Analisis Kepuasan Penggunaan Media Digital dalam Penilaian Kinerja ASN Pemerintah Kabupaten Banyuwangi - Ardhi Kurniawan; Rendra Eko Wismanu; Achmad Reza Rizky; Muhammad Iqbal Humam (Unitri Press, 2026)
The implementation of e-government in Indonesia serves as a crucial strategy for local governments to enhance the quality, efficiency, and transparency of public services. This study aims to evaluate employee satisfaction regarding the implementation of the E-Kinerja system and the Employee Performance Monitoring System (SIM-K) in Banyuwangi Regency using the E-Government Satisfaction (EGOVSAT) framework. The methodology employed is descriptive with a quantitative approach, involving 267 respondents selected through Proportional Stratified Random Sampling from a total population of 2,561 civil servants. Measurement was conducted based on five key dimensions: utility, reliability, efficiency, flexibility/customization, and risk. The results indicate that the overall user satisfaction score reached 3.710, with a Converted Interval Value (NIK) of 92.74, categorized as